Major diseases of ruminants in Nigeria - Maina, J.A. (International Livestock Centre for Africa, 1984)
Presents a brief account of the most important diseases of cattle and small ruminants in Nigeria. Lists the local name, disease group and incidence of the common diseases of small ruminants in northern Nigeria.